EFFICIENCY MARKET HYPOTHESIS, RANDOM WALK THEORY, AND FINANCIAL RATIOS-STOCK RETURNS: A COMPARATIVE STUDY OF BANKS IN INDONESIA, INDIA, AND CHINA IN THE POST-COVID ERA - ADININGSIH, TRIANA EVA (Universitas Airlangga, 2023)
This research aims to analyze how financial ratios affect firm value, utilizing the Efficiency Market Hypothesis and Random Walk Theory for analysis. It focuses on banking sector companies listed on the Indonesia Stock Exchange (XIDX), India Stock Exchange (XBOM), and China Stock Exchange (XSHG) from 2022 to 2023. This quantitative study employs purposive sampling, resulting in 184 firm- year samples, with data gathered from annual reports. Regression analysis using SPSS version 26 is the chosen method. The findings suggest that India has the most efficient market, while Indonesia aligns with the random walk theory, indicating weaker market efficiency. Notably, variables like